Financial development in the countries of the regional comprehensive economic partnership - Thi Phuong Thuy Duong (Вестник университета)
This study has identified the factors affecting the financial development of a country, thereby measuring the financial development process of countries of The Regional Comprehensive Economic Partnership in the period 2000–2020 through the construction of the Index aggregate of Financial Development for these countries. The study used Principal Components Analysis to provide a more quantitative, synthetic and harmonized view of financial development when combining 13 different representative indicators, including to the share of the contribution of each of these indicators to the overall index. These indicators represent each group of intermediaries, financial institutions and financial market groups in terms of depth, efficiency and stability, helping to reflect all aspects of the financial system in a holistic way. This will contribute to a clearer definition of the role and relationship between financial development and economic growth in The Regional Comprehensive Economic Partnership’s countries, a relationship that is still poorly researched.